Pengaruh Faktor Sosial Demografi Terhadap Produktivitas Dan Kesejahteraan Perajin Ukiran Kayu Di Kecamatan Ubud Kabupaten Gianyar - Sawitri, Ni Luh Dewi Mas; Suyana Utama, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Potential industrial sectors developed in Bali is the wood processing industry and articles of wood. Wood carving handicrafts industry which is in the District of Ubud Gianyar regency especially expected to improve the productivity and welfare of artisans carved wood. Low labor productivity is one of the serious problems in the industrial sector. This study aims to analyze how the influence of socio-demographic factors on the productivity and welfare of wood carving artisans in the district of Ubud Gianyar regency. Source of data used, there are two, namely primary data obtained from interviews directly to artisans carved wood and secondary data obtained from the Office of National Statistics Agency Gianyar Department of Trade and Industry and Gianyar. Methods of data collection is interview, observation and questionnaire. The analytical tool used is the analysis Structural equation (SEM) with Alternative Partial Least Square PLS (Component Based SEM). The number of samples taken were 96 samples, with a probability sampling method, in particular proportionate stratified random sampling. From the analysis of the research that the respondents' education up to junior level, almost all respondents have work experience of 21-30 years age range of 31-40 years and the number of family members covered by the respondents as many as four people. While the results of PLS ??data showed that socio-demographic factors have a significant effect on the productivity and welfare of wood carving artisans in the district of Ubud Gianyar, Productivity affect the well-being and productivity significantly contribute to mediate socio-demographic factors on the welfare in the District of Ubud Gianyar regency.
Keywords: Social Demography; Productivity; Welfare